459 Saudi Iranian Conflict in English and Arabic Translated News Reports - Abdul-Ameer, Muhannad Hadi; Al-Romany, Tahseen Ali Hussein (lark, 2019)
AbstractThe present study aims at investigating the Arabic translations of several English news reports on Saudi Iranian conflict to show translators draw on their ideological positioning in introducing events. In the present study, Appraisal Theory and Fairclough's trilateral model of Critical Discourse Analysis have been used to compare the English source texts with their translations into Arabic. The examples have been selected from BBC news reports published in the BBC Website at different dates. The major purpose of this study is to merely highlight the linguistic features of news reports about the Saudi Iranian conflict.
Keywords: CDA; deviation; ideological positioning; down-scale; up-scale; conflict; News translations